Praxis towards sustainable empowering learning environments in South Africa - Francis, Dennis A; Mahlomaholo, Mahlomaholo Geoffrey (Sechaba); Nkoane, Molebatsi Milton (UJ Press, 2010)
This collection presents some of the best peer-reviewed papers from a conference with the theme "Creating sustainable empowering learning environments through scholarship of engagement".